2021
DOI: 10.1111/cge.14038
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome sequencing identifies rare germline variants enriched in cancer related genes in first degree relatives of familial pancreatic cancer patients

Abstract: First-degree relatives (FDRs) of familial pancreatic cancer (FPC) patients have increased risk of developing pancreatic ductal adenocarcinoma (PDAC). Investigating and understanding the genetic basis for PDAC susceptibility in FPC predisposed families may contribute toward future risk-assessment and management of high-risk individuals. Using a Danish cohort of 27 FPC families, we performed whole-genome sequencing of 61 FDRs of FPC patients focusing on rare genetic variants that may contribute to familial aggre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 69 publications
1
7
0
Order By: Relevance
“…The hypergeometric test showed very high significance ( p < 1e‐22) for the observed overlaps. Finally, we tested overlaps between the 821 PTV genes with our recently reported 448 PTV genes detected in first‐degree relatives of FPC patients (Tan et al., 2021b). There were a total of 62 overlaps observed leading to an extremely high statistical significance (hypergeometric p < 1e‐22).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The hypergeometric test showed very high significance ( p < 1e‐22) for the observed overlaps. Finally, we tested overlaps between the 821 PTV genes with our recently reported 448 PTV genes detected in first‐degree relatives of FPC patients (Tan et al., 2021b). There were a total of 62 overlaps observed leading to an extremely high statistical significance (hypergeometric p < 1e‐22).…”
Section: Resultsmentioning
confidence: 99%
“…Nonsense and frameshift variants like PTVs and nonsynonymous variants that change the sequence and structure of coding proteins reduce the production of ECM proteins to impair matrix integrity, composition, and assembly due to quantitative ECM defects (Lamandé & Bateman, 2020). In a recent WGS study, we have observed a significant enrichment of the ECM pathway by genes carrying rare nonsynonymous variants in first-degree relatives of FPC patients (Tan et al, 2021b). Moreover, a recent network-based analysis of gene expression data on FPC and sporadic pancreatic cancer patients reported increased activity in extracellular structure and ECM organization (Tan et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, recently, some frameshift mutations of BRD3 have been found in GC[ 25 ]. Also, Tan et al [ 26 ] found that BRD3 was among the top six driver genes for familial aggregation of PDAC through whole-genome sequencing. That means unlike BRD2/4, BRD3 may function in GI cancer through a different mechanism.…”
Section: Bet Proteins In Gi Cancersmentioning
confidence: 99%